Economic Linkages, Relative Scarcity, and Commodity Futures Returns - Casassus, Jaime; Liu, Peng; Tang, Ke (Review of Financial Studies, 2013)
This paper shows that economic linkages among commodities create a source of long-term correlation between futures returns. We extend the theory of storage to a multi-commodity level and find that the convenience yield of a commodity depends on its relative scarcity with respect to other related commodities. This implies a feedback effect between commodities that is necessary to replicate the upward-sloping correlation term structure of futures returns observed for related commodities. We present a multi-commodity affine model that validates our theoretical predictions and considerably reduces the pricing errors in out-of-sample crack spread options.